Moving Pedagogy Outside: Reading a Graduate English Course with the Concepts of Fort Pedagogy, Indigenous Métissage, and the wâhkôhtowin Imagination - Schamuhn Kirk, Deborah (Canadian Journal of Education / Revue canadienne de l'éducation, 2025)
Where do we learn? What are our experiences of relationships in those contexts? Could teaching a course outside activate the wâhkôhtowin imagination? Can walking begin to repair relationships? Donald suggests that it can; and yet, another of the concepts Donald discusses, that of fort pedagogy, cautions us to listen and not claim. Is it possible for me, a White descendent of European immigrants, to learn from the wâhkôhtowin imagination without re-enacting fort pedagogy? In this article, I examine possibilities for anti-colonial pedagogy as I reflect on a student’s learning experiences—my own—from my dual positionality as PhD student and English literature instructor. Thinking alongside Indigenous Métissage (Donald, 2009, 2012), fort pedagogy (Donald, 2009), and the wâhkôhtowin imagination (Donald, 2021), I examine my experiences in an innovative graduate English course taught largely outside and consider ways pedagogy can shift relationships to place and to one another.